The Danish tax on saturated fat. Short run effects on consumption and consumer prices of fats - Jørgen Dejgård Jensen; Sinne Smed (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
Denmark introduced a new tax on saturated fat in food products with effect from October 2011. The objective of this paper is to make an effect assessment of this tax for some of the product categories most significantly affected by the new tax, namely fats such as butter, butter-blends, margarine and oils. This assessment was done by conducting an econometric analysis on weekly food purchase data from a large household panel dataset (GfK ConsumerTracking Scandinavia), spanning the period from January 2009 until December 2011.The econometric analysis suggest that the introduction of the tax on saturated fat in food products has had some effects on the market for the considered products, in that the level of consumption of fats dropped by 10 – 20%. Furthermore, the analysis points at shifts in demand from high-price supermarkets towards low-price discount stores – a shift that seems to have been utilized by discount chains to raise the prices of butter and margarine by more than the pure tax increase. Due to the relatively short data period with the tax being active, interpretation of these findings from a long-run perspective should be done with considerable care. It is thus recommended to repeat – and broaden – the analysis at a later stage, when data are available for a longer period after the introduction of the fat tax.
Keywords: 330; fat tax; demand response; price response; retail sales